Global Perspectives: Exploring Disruptive Technology Challenges for Consumers in Sub-Saharan Africa - Jet Mboga; Sonia Ammar; Mary Mboga (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2022)
The Base of Pyramid markets in Sub-Saharan Africa face challenges such as poverty, poor infrastructure, illiteracy, and government corruption. This paper examines and presents an analytical review of the difficulties among consumers in Sub-Saharan Africa using academic institutions in Kenya to illustrate disruptive technology. Sub-Saharan Africa is faced with practical challenges with disruptive technology. Qualitative analysis is conducted among a sample from Kenya to assess the validity of challenges faced in academia. The authors use stratified sampling to select the local population and reach higher precision with a response rate of 85%. The qualitative analysis findings confirm a positive relationship between smart devices and network reliability, online teaching, online grade book, and virtual learning. The authors conclude that network reliability is the most challenging, especially for higher education institutions moving forward with adopting mobile learning. There exists a research gap in the literature on the Sub-Saharan Context. The challenges of disruptive technology and academia within Sub-Saharan Africa were limited to Kenya. Further research by practitioners and scholars can explore the challenges of disruptive technology in Sub-Saharan Africa.